Caracterização psicossocial do paciente do CAPS I de Mirassol/SP - Geantomasse, Fausto Martins (2017)
Psychosocial Care Centers (CAPS) are institutions designed to accommodate patients with mental disorders, stimulate social and family integration, support autonomy seeking initiatives and provide medical and psychological care. Objective: This study has the aim of describing the clinical, sociodemographic and psychosocial characteristics of the users of the Psychosocial Care Center I (CAPS I) in the city of Mirassol, São Paulo, Brazil, between 2006 and 2016. Method: As far as the methods are concerned, this is a descriptive documentary study. A total of 668 medical records of patients who attended or have been attending CAPS I were analyzed. Data collection was consisted of 25 questions, including identification, sociodemographic and clinical data. The analyzes were descriptive, since all medical records were analyzed in the stipulated period. The project was approved by the Ethics Committee of the Medical School of São José do Rio Preto (opinion nº 1,377,417). Results: Regarding the results, 337 (50.45%) of the patients were female; 578 (86.53%) were adults between 19 and 59 years old; 376 (56.28%) had completed elementary education; 258 (38.62%) were Catholics; 265 (39.67%) were unmarried and 222 (33.23%) were married; 276 (41.32%) have already undergone at least one psychiatric hospitalization; 361 (54.05%) patients have a family history of mental problems; 163 (24%) were in care and 375 (53.14%) were discharged by evasion; Depressive symptoms were found in 200 (29.910%) patients; alcohol and drug abuse in 190 (28.46%) patients and psychotic symptoms in 150 (22.05%) patients; 600 (89.82%) patients used psychotropic medication. As far as gender is concerned, the most frequent diagnosis in females was depressive disorder (90 patients or 26.67% of them) and, in males, schizophrenia spectrum disorder (84 patients or 25.37% of them). Conclusion: Therefore, the CAPS attended patients with varied complaints and with several personal characteristics.